Hubungan Kadar HbA1c pada Pasien Diabetes Melitus Tipe II dengan Kejadian Azotemia di Rumah Sakit Angkatan Laut Dr. Ramelan Surabaya - VIOLITA PUTRI MURSANDI; SUWARNO; MOHAMMAD FATHI ILMAWAN (Universitas Hang Tuah, 2020)
ABSTRACT Background : Diabetes mellitus is chronic condition of elevated blood sugar levels, which can lead to complication due to uncontrolled sugar levels which is measured by HbA1c level parameters, affecting microvascular conditions, one of which is in the kidneys, which results in decreased kidney function characterized by elevated creatinine serum and BUN levels called by azotemia. In 2011 as many as 49.677 individuals began treatment for kidney failure which caused by diabetes, and around 228.934 people with various ages within kidney failer due to diabetes do dialysis and kidney transplantation. Methods : This observational analytic study was conducted by using cross sectional study design, by taking secondary data from the medical record files of diabetes mellitus type II patients who are doing outpatient care at the Diabetes Clinic Dr. Ramelan Naval Hospital Surabaya. Patients with a diagnosis of diabetes mellitus type II for at least five years will be the inclusion criteria of case samples. Bivariate analysis was performed using Spearman Correlation Test. Results : The results also showed that there were 19 people without azotemia and 21 people with azotemia. Blood sugar control which one of risk factor of azotemia by measuring HbA1c levels results 6 people with HbA1c <7; 21 people with HbA1c 7.19.0; and 13 people with HbA1c> 9.0. Spearman correlation test showed a significant value of p=0,512 with correlation coefficient 0.107. Conclusion: there is no relationship between HbA1c levels of type II diabetes mellitus patients with the incidence of azotemia